An Erg11 lanosterol 14-α-demethylase-Arv1 complex is required for Candida albicans virulence. - Michelle L Villasmil; Antonio Daniel Barbosa; Jessie Lee Cunningham; Symeon Siniossoglou; Joseph T Nickels (PLoS ONE)
Azole resistant fungal infections remain a health problem for the immune compromised. Current therapies are limited due to rises in new resistance mechanisms. Therefore, it is important to identify new drug targets for drug discovery and novel therapeutics. Arv1 (are1 are2 required for viability 1) function is highly conserved between multiple pathogenic fungal species. Candida albicans (C. albicans) cells lacking CaArv1 are azole hypersusceptible and lack virulence. Saccharomyces cerevisiae (S. cerevisiae) Scarv1 cells are also azole hypersusceptible, a phenotype reversed by expression of CaArv1, indicating conservation in the molecular mechanism for azole susceptibility. To define the relationship between Arv1 function and azole susceptibility, we undertook a structure/function analysis of ScArv1. We identified several conserved amino acids within the ScArv1 homology domain (ScAhd) required for maintaining normal azole susceptibility. Erg11 lanosterol 14-α-demethylase is the rate-limiting enzyme in sterol biosynthesis and is the direct target of azole antifungals, so we used our ScArv1 mutants in order to explore the relationship between ScArv1 and ScErg11. Specific ScArv1 mutants ectopically expressed from a low copy plasmid were unable to restore normal azole susceptibility to Scarv1 cells and had reduced Erg11 protein levels. Erg11 protein stability depended on its ability to form a heterodimeric complex with Arv1. Complex formation was required for maintaining normal azole susceptibility. Scarv1 cells expressing orthologous CaArv1 mutants also had reduced CaErg11 levels, were unable to form a CaArv1-CaErg11 complex, and were azole hypersusceptible. Scarv1 cells expressing CaArv1 mutants unable to interact with CaErg11 could not sustain proper levels of the azole resistant CaErg11Y132F F145L protein. Caarv1/Caarv1 cells expressing CaArv1 mutants unable to interact with CaErg11 were found to lack virulence using a disseminated candidiasis mouse model. Expressing CaErg11Y132F F145L did not reverse the lack of virulence. We hypothesize that the role of Arv1 in Erg11-dependent azole resistance is to stabilize Erg11 protein level. Arv1 inhibition may represent an avenue for treating azole resistance.